Association of Axial Length and Refraction with Near Horizontal Heterophoria in Chinese Children: An Observational Cross-Sectional Study - Xiaoqin Chen; Yanglin Jiang; Qian Fan; Lihua Li; Wenli Lu; Yan Wang (Journal of Ophthalmology)
Purpose. To evaluate the association of near heterophoria with refraction and axial length (AL) in Chinese school children. Methods. This school-based cross-sectional study included 15,081 Chinese primary school children (grades 1–6) examined during 2017. Near heterophoria was measured at 33 cm using the Maddox rod and prism test. Noncycloplegic refraction and AL were also measured. A generalized additive model with a Gaussian link was used to determine the association of near heterophoria with refraction and AL. Analyses were adjusted for age to account for differences in the age distribution of the sample. Results. Overall, data were analyzed for 11,013 students ranging in age from 6 to 13 years. The most common type of near heterophoria was exophoria (64.96%), the proportion and value of which increased according to grade. Exophoria accounted for 62.53% (2,328/3,723), 65.03% (2,501/3,846), and 67.51% (2,325/3,444) of near heterophoria cases for grades 1-2, grades 3-4, and grades 5-6, respectively. Prism diopter (PD) values for near heterophoria in these grades were −6.30 ± 3.69, −6.81 ± 4.01, and −8.32 ± 5.12 PD, respectively. The average spherical equivalent (SE) in children with orthophoria was 0.23 D and 0.25 D lower than those in children with exophoria and esophoria, respectively (P<0.001). The mean AL in children with orthophoria was 0.11 mm shorter than that in children with either exophoria or esophoria (P<0.001). Near heterophoria exhibited a significant correlation with refraction and AL, irrespective of age. Conclusions. Exophoria represents the most common type of near heterophoria in children. Children with more severe near heterophoria, whether exophoria or esophoria, exhibited a higher degree of myopia and longer AL than those with relatively less severe near heterophoria. These results highlight the need for further, long-term investigation regarding the role of near heterophoria in visual development.